2016
DOI: 10.5812/numonthly.38052
|View full text |Cite
|
Sign up to set email alerts
|

Short-Period Influence of Chronic Morphine Exposure on Serum Levels of Sexual Hormones and Spermatogenesis in Rats

Abstract: BackgroundIncreased rates of addiction and its broad societal complications are well known. One of the most important systems that may malfunction in drug abusers is the reproductive system, and evaluating patients for this potential risk may lead to increased awareness.Materials and MethodsThirty 60-day-old male rats were divided into control and target groups. The target group underwent 5 mg/kg intraperitoneal injections of morphine twice a day while the control group underwent normal saline injections (at t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
6
0
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 14 publications
5
6
0
2
Order By: Relevance
“…Also the distribution of Leydig and Sertoli cells did not differ from the two groups. However, the dose of morphine administered was on average lower than in the other studies [138]. These findings are partially in agreement with a study of Cicero and colleagues, where morphine treatment did not induce histological changes in the testis of rats treated with morphine.…”
Section: Effects On Spermatogenesissupporting
confidence: 91%
See 1 more Smart Citation
“…Also the distribution of Leydig and Sertoli cells did not differ from the two groups. However, the dose of morphine administered was on average lower than in the other studies [138]. These findings are partially in agreement with a study of Cicero and colleagues, where morphine treatment did not induce histological changes in the testis of rats treated with morphine.…”
Section: Effects On Spermatogenesissupporting
confidence: 91%
“…Another study found reduced LH levels in rats chronically treated with morphine, but FSH and testosterone levels did not significantly differ compared to controls. However, in this study the morphine administered dose was relatively low [138].…”
Section: Effects On Testosterone Productionmentioning
confidence: 71%
“…Also, it may be due to decreased secretion of GnRH by the hypothalamus, or failure of the anterior pituitary to respond to GnRH stimulation. According to Carou et al [30], administration of camphor in rats caused slight reduction in levels of LH, FSH, and (GnRH) in vitro, while similar findings have also been reported in rats following morphine [31][32][33][34], and alcohol exposures [35,36].…”
Section: Discussionsupporting
confidence: 55%
“…Для вивчення впливу екзогенних та ендогенних факторів на репродуктивну систему, а саме на цільовий органматкунайдоцільнішим методом є експериментальне моделювання [1,7,16,19]. У ході наших досліджень було проведено порівняльний аналіз матки білого лабораторного щура та людини.…”
unclassified
“…Окремої уваги заслуговують дослідження присвячені впливу наркотичних анальгетиків на структуру жіночих статевих органів, зокрема на будову стінки матки [1,4,5,9]. Maryam Dehghan та співавтори досліджували вплив морфіну на матку вагітних щурів.…”
unclassified